Pengaruh Harga, Kualitas Produk, Citra Merek dan Promosi terhadap Keputusan Pembelian Smartphone Merek Oppo dengan Kepuasan Konsumen sebagai variabel Mediasi(Studi Kasus pada Mahasiswa Universitas Nusa Bangsa) - Saputra, Muhamad Riko Yanwar; Nia Sonani; Rumna, Rumna (Journal of Management and Bussines (JOMB), 2025)
This study aims to analyze the influence of price, product quality, brand image, and promotion on Oppo smartphone purchase decisions, with consumer satisfaction as a mediating variable among students at Nusa Bangsa University. The research method used a quantitative approach with a causal associative approach. The sample consisted of 147 respondents selected using purposive sampling. The research instrument, a Likert-scale questionnaire, was then tested for validity and reliability. Data analysis was performed using multiple linear regression and a mediation test using SPSS version 25. The results showed that price, product quality, brand image, and promotion had a positive and significant influence on purchase decisions. Furthermore, price, product quality, brand image, and promotion also significantly influenced consumer satisfaction. Furthermore, consumer satisfaction was shown to act as a mediating variable in strengthening the relationship between price, product quality, brand image, and promotion on purchase decisions. These findings confirm that a marketing strategy that emphasizes a combination of competitive pricing, superior quality, a strong brand image, and appropriate promotion can increase consumer satisfaction and purchase decisions.   Keywords: Price, Product Quality, Brand Image, Promotion, Consumer Satisfaction